Tricholoma tianshanense sp. nov., in Tricholoma sect. Caligata from Tianshan Mountains in China evidenced by morphological characters and phylogenetic analyses - Zhao, Zhen-Xi; Song, Jia-Ge; Senanayake, Indunil C.; Wu, Dong-Sheng; Wang, Guo-Qing; Xu, Biao (Phytotaxa, 2022)
A tricholoma-like fungus was collected from Tianshan Mountains, Xinjiang, China and the morphology and phylogenetic analyses based on sequences of Internal Transcribed Spacer (ITS) locus were carried. This taxon is characterized by the medium to large basidiomes, with fairly inconspicuous, cottony-woolly ring and red to brownish-red, scales gradually thinning out towards the marginal zone on the pileus, with rarely clamped, guttulated basidiospores. Our collections are different from known Tricholoma species and they formed a distinct subclade with strong statistical supports in phylogenetic analyses. Based on the morphology and phylogeny, we introduce our collections as a new taxon, Tricholoma tianshanense sp. nov. The description and illustrations are provided herein.